2010
DOI: 10.1093/gbe/evq035
|View full text |Cite
|
Sign up to set email alerts
|

Divergence Involving Global Regulatory Gene Mutations in an Escherichia coli Population Evolving under Phosphate Limitation

Abstract: Many of the important changes in evolution are regulatory in nature. Sequenced bacterial genomes point to flexibility in regulatory circuits but we do not know how regulation is remodeled in evolving bacteria. Here, we study the regulatory changes that emerge in populations evolving under controlled conditions during experimental evolution of Escherichia coli in a phosphate-limited chemostat culture. Genomes were sequenced from five clones with different combinations of phenotypic properties that coexisted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
94
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(104 citation statements)
references
References 47 publications
10
94
0
Order By: Relevance
“…The mutational degeneracy of changing RpoS levels reinforces the huge diversity in RpoS across the species E. coli (51,98). The similar effect on SPaNC is accompanied by very different phenotypic changes with, for example, hfq and spoT mutations (353). These secondary differences provide the ingredients for phenotypic diversification seen in populations and across the species.…”
Section: Metabolic and Regulatory Redundancy As An Ingredient Of Evolmentioning
confidence: 94%
See 3 more Smart Citations
“…The mutational degeneracy of changing RpoS levels reinforces the huge diversity in RpoS across the species E. coli (51,98). The similar effect on SPaNC is accompanied by very different phenotypic changes with, for example, hfq and spoT mutations (353). These secondary differences provide the ingredients for phenotypic diversification seen in populations and across the species.…”
Section: Metabolic and Regulatory Redundancy As An Ingredient Of Evolmentioning
confidence: 94%
“…The level of RpoS in the cell responds to external and internal stresses and is influenced by over 20 environmental signal inputs (142). The alternative input pathways controlling rpoS expression provide degenerate ways of affecting regulation, and indeed many alternative genes can change the particular regulatory circuit controlling RpoS levels (353). Even within a single adapting population, heterogeneities can arise, and regulatory mutations are the most frequent type in experimental evolution studies (52,264,353).…”
Section: Importance Of the Genotype In Determining The Nature Of Adapmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental evolution studies combined with genome resequencing have correlated specific mutations to phenotypic changes to demonstrate that these dynamic genome reorganizational events are tightly coupled to adaptive evolution (Herring et al 2006;Barrick et al 2009). Interestingly, several studies have reported that, along with metabolic and structural genes, mutations within regulatory genes are also adaptive (Harris et al 2009;Wang et al 2010), which suggests that altering gene regulatory programs is an effective strategy for adaptation over short time intervals. Despite benefits of efficient coordinate regulation due to operonization, there is a surprisingly low level of conservation in operon structures across organisms.…”
mentioning
confidence: 99%